Immunotherapy: Metal–Organic Framework Nanoparticles Induce Pyroptosis in Cells Controlled by the Extracellular pH (Adv. Mater. 19/2020). Issue 19 (11th May 2020) - Ploetz, Evelyn; Zimpel, Andreas; Cauda, Valentina; Bauer, David; Lamb, Don C.; Haisch, Christoph; Zahler, Stefan; Vollmar, Angelika M.; Wuttke, Stefan; Engelke, Hanna
Abstract : In article number 1907267, Stefan Wuttke, Hanna Engelke, and co‐workers describe how lipid‐coated metal–organic framework (MOF) nanoparticles are taken up by cells via endocytosis. Once inside the cell, the MOF nanoparticles are degraded depending on the extracellular pH. The degradation product leads to pyroptosis—a programmed cell death involving the immune system, in which the cell membrane is perforated with pores leading to cell lysis. Ultimately, the nanoparticles may be used for immunotherapy.